Hypothyroidism and rheumatoid arthritis: a two-sample Mendelian randomization study - Gao, Yang; Fan, Zheng-Rui; Shi, Fang-Yuan (Frontiers in Endocrinology, 2023)
Background Meta-analysis of genome wide association studies (GWAS) data showed that the relationship between hypothyroidism and rheumatoid arthritis (RA) risk remains under debate. This study is proposed to test the causal relationship of hypothyroidism and RA. Methods A two-sample Mendelian randomization (TSMR) analysis was employed to estimate the causality of hypothyroidism and rheumatoid arthritis in European ancestry and Asian ancestry. Integrating the effects generated by TSMR, functional annotations and noncoding variants prediction framework were applied to analyze and interpret the functional instrument variants (IVs). Results The results of inverse variance weighted method showed a strong significant causal relationship between hypothyroidism and risk of RA in European ancestry (odds ratio (OR) = 1.96; 95% confidence interval (CI) 1.49, 2.58; P < 0.001). The outcomes of MR-Egger, weighted median, weighted mode, and simple mode also showed hypothyroidism was significantly associated with increased risk of RA in European ancestry. The MR-PRESSO method also showed significant results (Outlier-corrected Causal Estimate = 0.70; standard error (SE) = 0.06; P < 0.001). Independent dataset and Asian ancestry dataset were applied to estimate and get the coincident results. Furthermore, we integrated the effect of variants in TSMR analysis, functional annotations, and prediction methods to pinpoint the single nucleotide polymorphism (SNP) rs4409785 as one of the causal variants, which suggested this variant could impact the binding of CTCF-cohesin to play a vital role in immune cells. Conclusions In this study, we prove that hypothyroidism is significantly causal associated with increased RA risk which has not been showing in previous studies. Furthermore, we pinpoint the potential causal variants in RA.